ISSR, RAPD and agronomic study in some F1 and F2 cotton genotypes - Noormohammadi Zahra (Acta biologica Szegediensis, 2011)
Cotton is an important economic crop plant with diploid and tetraploid cultivars. Hybridization is one of the main breeding strategies in cotton breeding producing new genotypes and also increasing the genetic diversity in cotton germplasm available. The present study considers agronomic and molecular study of genetic variations in thirteen F1 and F2 cotton genotypes (Gossypium hirsutum) obtained by crossing the cotton cultivars Bellizovar, No. 200, Siokra, Sindose and Tabladilla. Out of 30 RAPD primers used 19 primers produced 191 reproducible bands/loci out of which 63 bands were polymorph. Eight ISSR primers used produced 86 reproducible bands, out of which 27 bands were polymorph and 59 bands were monomorph. Some bands were present in the F1 progenies but absent in the F2 progenies of the same genotype. The mean values of gene diversity (H) and Shanon’s Information Indices (I) for ISSR markers in the F1 progenies were 0.27 and 0.40 respectively, while the same values in F2 progenies were 0.18 and 0.26 respectively. Similarly the mean values of H and I of the F1 progenies for RAPD markers were 0.07 and 0.11 respectively, while the same values in F2 progenies were 0.09 and 0.13 respectively. UPGMA and NJ dendrograms grouped the F1 and F2 progenies of Siokra X Belilzovar together, standing from the other genotypes due to their genetic differences. The use of present finding in planning future hybridization is discussed.